Sovereignty, democracy, and global civil society : state-society relations at UN world conferences - Friedman, Elisabeth J., 1966- (SUNY series in global politics., 2005)
Sovereignty, Democracy, and Global Civil Society explores the growing power of nongovernmental organizations (NGOs) by analyzing a microcosm of contemporary global state-society relations at UN World Conferences. The intense interactions between states and NGOs at conferences on the environment, human rights, women's issues, and other topics confirm the emergence of a new transnational democratic sphere of activity. Employing both regional and global case studies, the book charts noticeable growth in the ability of NGOs to build networks among themselves and effect change within UN processes. Using a multidimensional understanding of state sovereignty, the authors find that states use sovereignty to shelter not only material interests but also cultural identity in the face of external pressure. This book is unique in its analysis of NGO activities at the international level as well as the complexity of nation-states' responses to their new companions in global governance. Book jacket.